1991
DOI: 10.1002/1097-0142(19910715)68:2<242::aid-cncr2820680204>3.0.co;2-p
|View full text |Cite
|
Sign up to set email alerts
|

High-dose melphalan with 6-hydroxydopamine–purged autologous bone marrow transplantation for poor-risk neuroblastoma

Abstract: Long-term results are presented of 28 patients who were diagnosed with neuroblastoma at more than 12 months of age and who received melphalan 180 mg/m2 (n = 6) or 240 mg/m2 (n = 22) to consolidate remissions of Stage IV disease or to control refractory disease. Twenty-four patients also received dianhydrogalactitol 180 to 240 mg/m2, and 11 received total body irradiation 450 to 600 cGy. Autologous bone marrow transplantation (ABMT) was performed with marrow that was unpurged (n = 2) or purged ex vivo (n = 26) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…Our group adopted ASCT consolidation of HR-NB in the 1980s based on the concept that high-dose alkylators can overcome chemoresistance [ 10 , 11 ]. Subsequently, after promising results with high-dose cyclophosphamide in induction [ 12 ], as well as with 3F8 in phase I and II trials [ 13 , 14 ], we undertook a non-ASCT study using dose-intensive induction followed by consolidation with 3F8 [ 15 ] and local RT [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Our group adopted ASCT consolidation of HR-NB in the 1980s based on the concept that high-dose alkylators can overcome chemoresistance [ 10 , 11 ]. Subsequently, after promising results with high-dose cyclophosphamide in induction [ 12 ], as well as with 3F8 in phase I and II trials [ 13 , 14 ], we undertook a non-ASCT study using dose-intensive induction followed by consolidation with 3F8 [ 15 ] and local RT [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the 1980s and 1990s, studies in neuroblastoma suggested an improvement of outcome with myeloablative therapy in conjunction with autologous BM transplant [ 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 ]. It was the time when adult oncology was massively testing HDT strategies for solid tumors as previously reviewed.…”
Section: Why Only Neuroblastoma? the Original Mistakementioning
confidence: 99%
“…6-Hydroxydopamine (6-OHDA) was used in combination with ascorbic acid for ex vivo purging of bone marrow stem cells from neuroblastoma cells before autologous bone marrow transplantation [1]. Autoxidation of 6-OHDA leads to the formation of cytotoxic reactive oxygen species (ROS), and this process is enhanced in the presence of an excess of ascorbic acid by redoxcycling [2].…”
Section: Introductionmentioning
confidence: 99%